2011
DOI: 10.1016/j.jtcvs.2010.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the promoter of human leukocyte antigen class I in human esophageal squamous cell carcinoma and its histopathological characteristics

Abstract: HLA-I promoter hypermethylation was associated with loss of HLA-I antigen, which frequently occurred in primary tumors, especially in metastatic lymph node lesions, and was associated with patients' prognoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…However, just as it appears to be too much to ask the immune system augmented with vaccination to eradicate large, established tumors, it may also be difficult to use vaccines to stop the most quickly dividing, genetically unstable malignancies. Support for this idea has been published by several investigators who have demonstrated that the histologic grade of malignancy, a marker of aggressiveness, independent of the stage of disease, has been linked to increased immune suppression though loss of HLA expression, increased levels of immunosuppressive cytokines and immunosuppressive cells, and other mechanisms [64,[78][79][80][81][82] alluded to above.…”
Section: Vaccination In Less Aggressive Diseasementioning
confidence: 97%
“…However, just as it appears to be too much to ask the immune system augmented with vaccination to eradicate large, established tumors, it may also be difficult to use vaccines to stop the most quickly dividing, genetically unstable malignancies. Support for this idea has been published by several investigators who have demonstrated that the histologic grade of malignancy, a marker of aggressiveness, independent of the stage of disease, has been linked to increased immune suppression though loss of HLA expression, increased levels of immunosuppressive cytokines and immunosuppressive cells, and other mechanisms [64,[78][79][80][81][82] alluded to above.…”
Section: Vaccination In Less Aggressive Diseasementioning
confidence: 97%
“…Moreover, impaired MHC class I-mediated antigen presentation has been recognized as a major immune evasion mechanism in various cancers [8, 9, 5356]. The high frequency of loss of MHC class I has been reported in 92% of cervical cancers [57], 71% of breast cancers [58], 64% of non-small cell lung cancers [59], 67% of esophageal squamous cell carcinomas [60] and in others [61–65]. Various molecular mechanisms reported account for the loss of MHC class I, including loss of heterozygosity in HLA-A, -B, -C or B2M genes [66, 67]; somatic mutations in HLA, B2M, TAP1/2 or LMPs [67–71]; HLA gene methylation [72, 73]; post-translational changes in TAP1 [71]; and defective JAK-STAT pathway at the IFN-γ receptor signaling [74].…”
Section: Nlrc5-targeted Immune Evasion In Cancermentioning
confidence: 99%
“…It has been demonstrated that cancer cells use multiple strategies of immune evasion, including increased resistance to cytotoxic T-cell killing, induction of anergy in activated T cells, elimination of effector T cells, recruitment of regulatory immune cell subsets, and reduced recognition of tumor-associated antigens by effector T cells (2). Impaired MHC class I-mediated antigen presentation is a major immune evasion mechanism in cancer (3,4), with MHC class I loss reported in cervical cancer (92%) (5), penile cancer (80%) (6), breast cancer (71%) (7), nonsmall cell lung cancer (64%) (8), and esophageal squamous cell carcinoma (67%) (9), among others. Although a number of mechanisms have been described for HLA loss, including the loss of heterozygosity, HLA gene methylation, nonsense/ missense mutations, and loss of TAP1/2 or β2-microglobulin (B2M), the dominant underlying molecular mechanism seems to reside at the transcriptional level (10).…”
mentioning
confidence: 99%